Determinants of Employee Turnover Intention - Aburumman, Omar Jaber; Arabiat, Khuzama (Modern Perspectives in Economics, Business and Management Vol. 1, 2021)
This book chapter is divided into six sections and contains many papers related to employee turnover intention. These papers are independent and are not interrelated, and it's provided in different perspectives in terms of content and objective. Section One is an introduction that explains the content of the chapter. Section Two allows the readers to better understand employee turnover intention. Sections Three and Four present some factors that have the potential to influence employee turnover intention including human resource management practices (compensation, performance appraisal, promotion, and training & development) and career satisfaction. Section Five focuses on social exchange theory. This book chapter ends with section six which is also the conclusion that summarizes the content of this book chapter.